Effects of Treatment with Zinc Sulphate on the Oxidative Stress State during Chronic Exposure to Lead in Humans - Alabbassi G. Mustafa; Ismail k. Dawser; Numan A. Nawfal; Hussin A. Saad (College of Pharmacy / Mustansiriyah University, 2006)
Oxidative stress has been recently implicated in the pathogenesis of lead poisoning. Consequently, the potential protective effects of antioxidant agents had been raised. This study was designed to explore the potential protective effects of zinc against the oxidative stress due to chronic exposure to lead Lead-exposed workers were treated with 100mg zinc sulphate / day for 2 months, and the extent of oxidative stress was evaluated by measuring of erythrocytes and plasma content of GSH and MDA, in addition the Cu, Zn and Pb blood level were measured also. The results of this study showed that treatment with zinc sulphate significantly lowered MDA production and increased glutathione levels in plasma and erythrocytes. Blood lead levels, which were elevated significantly due to chronic exposure, showed a reproducible reduction after treatment with zinc sulphate, associated with improvement in copper and zinc levels in the plasma of lead workers. In conclusion, daily supplementation with zinc as antioxidant to lead exposed workers seems to be beneficial in the prevention of oxidative stress associated with chronic exposure.